Possibilities of establishing a construction cluster in Namangan region - S.S. Zokirov; M.A. Abdurakhmanov (Genius Publishing Group, 2022)
The factors and directions of regional construction cluster formation in the conditions of the need to ensure the innovative development of the construction industry are studied in the article.
Keywords: Construction industry; innovative development; investors